2009
DOI: 10.3892/or_00000347
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation and apoptosis induced by a Na+/H+ exchanger-1 (NHE-1) antisense gene on drug-resistant human small cell lung cancer cells

Abstract: Abstract. The goal of this study was to evaluate the effect of the Na + /H + exchanger-1 (NHE-1) antisense gene on drugresistant human small cell lung cancer (SCLC) cell proliferation and apoptosis. A recombinant NHE-1 antisense gene was transfected into drug-resistant human SCLC H446/CDDP cells. Intracellular pH (pHi) was measured with fluorescence spectrophotometry. Cell proliferation was assayed cytometrically, and expression of the apoptosis gene caspase-3 was assayed using immunohistochemistry. Apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…18 Our previous study indicated that certain interventions could restore SW480 and Hep-2R cell line's sensitivity to TRAIL by upregulating the cell surface expression of death receptors. 19,20 Therefore, further study is required to unravel the mechanism regulating TRAIL resistant signaling and to identify molecular switches that may set the system into the "apoptosis position." Previous study has indicated that targeting the sphingosine signaling could help to bring the misguided apoptosis back to the right track.…”
Section: Introductionmentioning
confidence: 99%
“…18 Our previous study indicated that certain interventions could restore SW480 and Hep-2R cell line's sensitivity to TRAIL by upregulating the cell surface expression of death receptors. 19,20 Therefore, further study is required to unravel the mechanism regulating TRAIL resistant signaling and to identify molecular switches that may set the system into the "apoptosis position." Previous study has indicated that targeting the sphingosine signaling could help to bring the misguided apoptosis back to the right track.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ion transporters NHE-1 is an ubiquitously expressed plasma membrane protein that plays an essential role in maintaining physiological pH i . Inadequate function of this transporter has been described in several cancer types, including esophageal cancer [13,16,[33][34][35][36][37]; therefore, NHE-1 emerged as a potential target in anti-cancer therapy [37,38]. We showed that, in the case of acute CSE exposure, higher concentrations of CSE increased NHE-1 activity in the metaplastic cells; this is presumably a defense mechanism by which the cells try to maintain the normal pH homeostasis.…”
Section: Discussionmentioning
confidence: 72%
“…Among the ion transporters NHE-1 is an ubiquitously expressed plasma membrane protein that plays an essential role in maintaining physiological pHi. Inadequate function of this transporter has been described in several cancer types, including esophageal cancer [13,16,[33][34][35][36][37]; therefore,…”
Section: Discussionmentioning
confidence: 99%